Pengaruh Kompetensi Sumber Daya Manusia, Penerapan Sistem Akuntansi Keuangan Daerah Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Organisasi Perangkat Daerah (OPD) Di Kota Mataram: - - Ni Made Yeni Parwati Tira Putri; Ni Nyoman Yuliati; Rusli Amrul (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This study aims to examine the influence of human resource competence, implementation of regional accounting systems and internal control systems on the quality of financial reports of regional apparatus organizations (OPD) in Mataram City. The research method used is the associative quantitative method.The population in the study used 39 OPDs in Mataram City. The sampling technique used is purposive sampling. The sample used in this study was 66. Data analysis used SPSS 25 with classical assumption tests and multiple linear regression. The results showed that Human Resource Competence and Implementation of Regional Financial Accounting Systems had a significant effect on the Quality of Financial Reports in OPDs in Mataram City, while the Internal Control System did not have a significant effect on the Quality of Financial Reports in OPDs in Mataram City